Development of Organic Rice Farming in the Amohalo Rice Field Area, Sub-district Baruga, District Baruga - Najwatul Alyah; Samsul Alam Fyka; Hidrawati Hidrawati (International journal of technology and education research, 2026)
This study aims to analyze the development of organic rice farming in the Amohalo rice field area, Baruga Village, Baruga District, and to identify the factors influencing its development. The research was conducted from October 2025 to February 2026. A descriptive qualitative method was employed in this study. The research location was selected purposively because the Amohalo rice field area is one of the centers for organic rice development in Kendari City. Respondents were determined using purposive sampling, consisting of organic rice farmers, farmer group leaders, community leaders, agricultural extension officers, officials from the Kendari City Agriculture Office, representatives from Bank Indonesia Southeast Sulawesi, and consumers of organic rice. Data used in this study included primary data obtained through observation and interviews, as well as secondary data collected from relevant institutions and literature sources. The results show that organic rice farming in the Amohalo rice field area has developed positively, indicated by the increasing implementation of organic cultivation practices, strengthened farmer institutions, and support from government and related institutions. The development of organic rice farming is influenced by several factors, including market access, cultivation technology, availability of production inputs, policy support, extension services, farmer institutions, transportation, and capital availability. Strengthening farmer capacity and continuous institutional support are needed to further enhance the sustainability of organic rice farming in the region. Keywords: organic rice, Farming development, Organic agriculture.